Study on Improving Clean Water Distribution System Using the Epanet 2.0 Application in Tiara Regency Housing Limbangan - Al Afghani, Mohammad Abidzar; Tahadjuddin, Tahadjuddin; Kartika, Nia (Jurnal Ilmiah Telsinas, 2025)
Tiara Regency Limbangan Housing is located in Limbangan village, Sukaraja District, Sukabumi Regency. This housing is one of the areas that is growing rapidly. As the number of residents and activities in the area increases, the need for an effective and efficient clean water distribution system is very important. However, the clean water distribution system at Tiara Regency Limbangan Housing is still uneven at several points. This research aims to simulate the clean water distribution system in the Epanet 2.0 application to find out the problems and solutions so that they run optimally. This study uses population data to determine the amount of discharge needed. Water discharge data from the reservoir to determine water availability. Existing data and pipeline details are used to analyze Epanet 2.0 so that the pressure value, and energy loss in each connection and pipeline can be known. The availability of main pipeline water 1 is 444,096 liters/day and the availability of mains pipeline water 2 is 425,952 liters/day. The water demand in main pipeline 1 reaches 321,595 liters/day while the water demand in main pipeline 2 reaches 284,335 liters/day. The results of the existing analysis showed that there were 88 connections with negative pressure at peak usage hours. Optimization is carried out by changing the diameter of the main pipe 1 from 3 inches to 4 inches.